2007
DOI: 10.1681/asn.2006070781
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Oxidation Protein Products Accelerate Renal Fibrosis in a Remnant Kidney Model

Abstract: Accumulation of plasma advanced oxidation protein products (AOPP) has been found in patients with chronic kidney disease. However, the biologic consequences of AOPP consumption on progression of renal disease still are unclear. For testing of the hypothesis that AOPP accelerate progression of chronic kidney disease, Sprague-Dawley rats were subjected to five-sixths nephrectomy (5/6 Nx) or to sham operation. Rats in each group were randomly assigned in three subgroups (n ‫؍‬ 30 in each group) and treated with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
112
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(114 citation statements)
references
References 41 publications
2
112
0
Order By: Relevance
“…16 It has been reported that in patients with chronic kidney disease, AOPPs act on redox-sensitive inflammatory pathways to promote renal fibrosis and accelerate disease progression. 17 In AKI such as that after coronary artery bypass graft surgery, AOPPs can be used as prognostic biomarkers to measure the recovery progress. 18 Additionally, ROS not only elicit injury to reperfused tissue directly, they also amplify the effect of injury of ROS through peroxidation (oxidative stress).…”
Section: Discussionmentioning
confidence: 99%
“…16 It has been reported that in patients with chronic kidney disease, AOPPs act on redox-sensitive inflammatory pathways to promote renal fibrosis and accelerate disease progression. 17 In AKI such as that after coronary artery bypass graft surgery, AOPPs can be used as prognostic biomarkers to measure the recovery progress. 18 Additionally, ROS not only elicit injury to reperfused tissue directly, they also amplify the effect of injury of ROS through peroxidation (oxidative stress).…”
Section: Discussionmentioning
confidence: 99%
“…The creatinine clearance rate (Ccr) was calculated as described and factored for body weight (Li et al 2007a). 24 hr UAE was measured using the Coomassie Blue method (Lott et al 1983).…”
Section: Renal Function and Urine Examinationmentioning
confidence: 99%
“…3!0 . 3 mm areas of the tubulointerstitium for each kidney (Li et al 2007a). The intensity of glomerular staining of TGFB1, CCL2, and fibronectin was evaluated at a 400!…”
Section: Renal Immunohistochemical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the sensitivity, stability, convenience and cost of detection, the role of AOPPs in predicting the severity of oxidative stress and disease prognosis has become increasingly important. AOPPs may accelerate renal fibrosis and atherosclerosis, and may be detrimental to the progression of chronic kidney disease (22)(23)(24). In postmenopausal women, AOPPs are negatively associated with a reduced bone mineral density, which increases an individual's risk of developing osteoporosis (25).…”
Section: Introductionmentioning
confidence: 99%